L2hgdh Deficiency Accumulates l-2-Hydroxyglutarate with Progressive Leukoencephalopathy and Neurodegeneration - Ma, Shenghong (Mol Cell Biol, 2017)
l-2-Hydroxyglutarate aciduria (L-2-HGA) is an autosomal recessive neurometabolic disorder caused by a mutation in the l-2-hydroxyglutarate dehydrogenase (L2HGDH) gene. In this study, we generated L2hgdh knockout (KO) mice and observed a robust increase of l-2-hydroxyglutarate (L-2-HG) levels in multiple tissues. The highest levels of L-2-HG were observed in the brain and testis, with a corresponding increase in histone methylation in these tissues. L2hgdh KO mice exhibit white matter abnormalities, extensive gliosis, microglia-mediated neuroinflammation, and an expansion of oligodendrocyte progenitor cells (OPCs). Moreover, L2hgdh deficiency leads to impaired adult hippocampal neurogenesis and late-onset neurodegeneration in mouse brains. Our data provide in vivo evidence that L2hgdh mutation leads to L-2-HG accumulation, leukoencephalopathy, and neurodegeneration in mice, thereby offering new insights into the pathophysiology of L-2-HGA in humans.